Can the Integration of Rural Industries Help Strengthen China’s Agricultural Economic Resilience? - Zhou, Jie; Chen, Haipeng; Bai, Qingyun; Liu, Linxin; Li, Guohong; Shen, Qianling (Agriculture (Basel), 2023)
Rural industrial integration is the key to promoting the development of rural industrial restructuring and modernization, and plays a vital role in improving agricultural economic resilience. Based on the evaluation index system of agricultural economic resilience and the level of rural industrial integration development, respectively, this paper uses panel data from 30 provincial administrative regions in China from 2000 to 2020 to empirically test the impact of rural industrial integration development on agricultural economic resilience by using an individual fixed-effects model and a mediating-effects model. The results show that rural industrial integration significantly contributes to enhancing agricultural economic resilience, and the conclusion still holds after a series of robustness tests. There is dimensional and regional heterogeneity in the impact of rural industrial integration on agricultural economic resilience, and the strength of the promotion effect by dimension is in the order of adaptive adjustment capacity, transformation and innovation capacity, and resilience to recovery capacity. In the eastern and central regions, the promotion effect of rural industrial integration on agricultural economic resilience is more significant. In the main food-producing areas, the promotion effect of rural industrial integration on resilience to recovery is significantly slighter than that of non-food-producing regions. Mechanism analysis indicates that regional industrial structure optimization is an essential channel for rural industrial integration to enhance the resilience of the agricultural economy. On this basis, in order to strengthen agricultural economic resilience, provinces should actively explore differentiated industrial integration policies to enhance industrial structure optimization and upgrading, stimulate agricultural economic vitality, and foster the development of China’s agricultural modernization.